2022
DOI: 10.1080/21655979.2021.2003942
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-22-3p targeted regulating transcription factor 7-like 2 (TCF7L2) constrains the Wnt/β-catenin pathway and malignant behavior in osteosarcoma

Abstract: Various studies have manifested that microRNAs (miRNAs) are involved in the modulation of the occurrence and development of osteosarcoma (OS). However, whether miR-22-3p is associated with OS growth remains unclear. In the study, the potential molecular mechanisms of miR-22-3p in OS was explored. It was affirmed that miR-22-3p was associated with distant metastasis and tumor size in OS patients, and reduced in OS tissues and cells while transcription factor 7-like 2 (TCF7L2) was elevated. Elevated miR-22-3p re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…The SRSF3 gene (serine and arginine rich splicing factor 3) has been reported to play a critical role in cell proliferation by promoting the G2/M transition, and preventing the death of apoptotic cells in cancers where it functions as an oncogene [ 42 ]. TCF7L2 (transcription factor 7 like 2) is a key factor in the Wnt signaling pathway, one of the 3 main cancer stem cell (CSC) pathways, and functions as an oncogene in osteosarcoma [ 43 ]. Transactivated by ERK/JNK-c-JUN/c-FOS, FOXP1 (forkhead box P1) drives osteosarcoma development by regulating the cascade of p53-P21/RB signaling [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The SRSF3 gene (serine and arginine rich splicing factor 3) has been reported to play a critical role in cell proliferation by promoting the G2/M transition, and preventing the death of apoptotic cells in cancers where it functions as an oncogene [ 42 ]. TCF7L2 (transcription factor 7 like 2) is a key factor in the Wnt signaling pathway, one of the 3 main cancer stem cell (CSC) pathways, and functions as an oncogene in osteosarcoma [ 43 ]. Transactivated by ERK/JNK-c-JUN/c-FOS, FOXP1 (forkhead box P1) drives osteosarcoma development by regulating the cascade of p53-P21/RB signaling [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…[41][42][43] It has been confirmed that miR-22-3p can inhibit osteosarcoma progression by targeting and regulating Transcription Factor 7 Like 2. [44] Low miR-125-5p expression is associated with the progression of various tumors. [45][46][47] In addition, miR-125-5p inhibits the proliferation and invasion of breast cancer cells by targeting and regulating Tumor Protein D52.…”
Section: Discussionmentioning
confidence: 99%
“…The Wnt/β-Catenin signaling pathway facilitates cancer cells proliferation and differentiation, which serves a fundamental role in tumorigenesis [ 41 ]. Recent evidence shows that several microRNAs could regulate the Wnt/β-Catenin pathway, for instance, by miR-22-3p, miR-30b and miR-377-3p in OS [ 42–44 ]. Meanwhile, miR-331-3p up-regulation in pancreatic cancer cells has been shown to activate the Wnt/β-Catenin pathway [ 13 ].…”
Section: Discussionmentioning
confidence: 99%